Paradigm shift from a liquidation culture to a corporate rescue culture in Malaysia: A legal review - Chen, Thim Wai (INSOL International and John Wiley & Sons Ltd, 2020)
The company law landscape in Malaysia has witnessed a significant change in its insolvency law with the adoption of two new corporate rescue mechanisms, the corporate voluntary arrangement and judicial management under the Companies Act 2016 (CA 2016), which has repealed the Companies Act 1965 (CA 1965). Previously, the insolvency laws under the CA 1965 were based on the traditional pro‐creditor laws of winding up and receivership, which embodied the liquidation culture. This article examines the transition of the insolvency laws in Malaysia from a liquidation culture under the CA 1965 to a corporate rescue culture under the CA 2016. It also reviews the necessary changes to the pro‐creditor laws, which are preserved under the CA 2016 in order to accommodate the pro‐debtor laws with the introduction of the corporate rescue mechanisms, which came into force on March 1, 2018. Through comparative and critical analysis of similar laws in the United Kingdom and Singapore, this article argues that while the corporate rescue mechanisms are regarded as pro‐debtor however the review reveals that the position of secured creditors are impeding its application and reforms ought to be considered